Negotiating Gender in the Digital Age: Young People and the Representation of Femininity and Masculinity on Social Media - Scarcelli, Cosimo Marco; Farci, Manolo (Italian Sociological Review, 2024)
The rise of visual-based social media platforms such as Instagram, Snapchat, and TikTok has transformed the digital landscape and become increasingly important for young people who use these platforms as discursive spaces for their self-presentation. Through these platforms, young people engage with dominant norms and societal expectations surrounding gender and attempt to perform a successful visual self that reflects their overall identity. However, these norms and expectations can lead to the perpetuation of gender stereotypes and conventional beauty standards. On the other hand, social media also provide a space for challenging traditional gender norms and celebrating non-conforming identities. This study focuses on exploring how young people negotiate and make sense of femininity and masculinity in the digital environment through the creation of fictitious social media profiles using mood boards. Through the analysis of the resulting characters created by our participants, we explored how these visual artefacts tend to reflect or subvert current stereotypes of masculinity and femininity.